2010
DOI: 10.1139/x10-061
|View full text |Cite
|
Sign up to set email alerts
|

Fire, climate change, and forest resilience in interior AlaskaThis article is one of a selection of papers from The Dynamics of Change in Alaska's Boreal Forests: Resilience and Vulnerability in Response to Climate Warming.

Abstract: In the boreal forests of interior Alaska, feedbacks that link forest soils, fire characteristics, and plant traits have supported stable cycles of forest succession for the past 6000 years. This high resilience of forest stands to fire disturbance is supported by two interrelated feedback cycles: (i) interactions among disturbance regime and plant-soil-microbial feedbacks that regulate soil organic layer thickness and the cycling of energy and materials, and (ii) interactions among soil conditions, plant regen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
123
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(134 citation statements)
references
References 64 publications
4
123
0
Order By: Relevance
“…Our simulations suggest a 22 % relative reduction with a 100 % increase in burn area. However, it has been suggested that an intensifying fire regime may not just increase deciduous fractions, but lead to an alternate stability point of deciduous forest dominance (Johnstone et al, 2010a). This would tend to amplify our modeled temperature effects, although a landscape dominated by deciduous trees may display entirely different fire dynamics.…”
Section: Caveatsmentioning
confidence: 88%
“…Our simulations suggest a 22 % relative reduction with a 100 % increase in burn area. However, it has been suggested that an intensifying fire regime may not just increase deciduous fractions, but lead to an alternate stability point of deciduous forest dominance (Johnstone et al, 2010a). This would tend to amplify our modeled temperature effects, although a landscape dominated by deciduous trees may display entirely different fire dynamics.…”
Section: Caveatsmentioning
confidence: 88%
“…By killing overstory trees and initiating succession, fires modify vegetation composition over a period of decades (Johnstone and Kasischke 2005;Goetz et al, 2007; Published by Copernicus Publications on behalf of the European Geosciences Union. Johnstone et al, 2010) that, in turn, influences surface albedo Lyons et al, 2006) and sensible and latent heat fluxes (Liu et al, 2005;Amiro et al, 2006;Lee et al, 2011). These fire-ecosystem interactions have the potential to modify regional climate (Rogers et al, 2013) and influence boreal forest species composition (Goetz et al, 2007;Johnstone et al, 2011;Barrett et al, 2011;Mann et al, 2012;Hollingsworth et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…There is also similar evidence from boreal forests of Alaska that with increasing fire disturbance, tree stand species composition shifts from conifer-dominated to comprising more early-successional deciduous trees, mainly birch and aspen (Johnstone et al 2010). In Alaska, this has been connected to the consumption of soil humus layer by fire that alters seedbed conditions (Johnstone et al 2010). As fire activity is considered to increase in some regions of circumboreal forests (Westerling et al 2006;Flannigan et al 2009) due to changing climate (IPCC 2014), in such areas a landscape-level regime shift is predicted from conifer-dominated forests to forest that contain more deciduous trees (Johnstone et al 2010).…”
Section: Discussionmentioning
confidence: 55%
“…This basic knowledge of Fennoscandian tree autecology and post-fire succession is confirmed by comparing mechanistic simulations of forest landscape structure with field measurements (Pennanen 2002;Pennanen and Kuuluvainen 2002). There is also similar evidence from boreal forests of Alaska that with increasing fire disturbance, tree stand species composition shifts from conifer-dominated to comprising more early-successional deciduous trees, mainly birch and aspen (Johnstone et al 2010). In Alaska, this has been connected to the consumption of soil humus layer by fire that alters seedbed conditions (Johnstone et al 2010).…”
Section: Discussionmentioning
confidence: 72%